Efek Pasar Monopoli pada Ekonomi Indonesia: Peluang dan Dampaknya - Maduwu, Aan Krisnawan; Pratama, Nico; Tampubolon, Arsyaf (MTU PRESS, 2024)
The monopoly market in Indonesia has a significant impact on the dynamics of the national economy. Monopoly practices, which are characterized by the dominance of one or a few companies in a sector, can cause market distortion, hinder business competition, and have an impact on consumer welfare. This article examines the effects of monopoly markets on the Indonesian economy with a focus on the opportunities and challenges they pose. Using a qualitative descriptive research method based on literature review, this article finds that monopoly, especially by State-Owned Enterprises (BUMN), has a double impact: on the one hand it supports economic stability and infrastructure development, but on the other hand it can reduce innovation and market efficiency. Tighter regulations and effective law enforcement are needed to prevent the negative impacts of monopoly and encourage healthy and sustainable competition.